Highlights for the Management of a Child with Proteinuria and Hematuria - Jyothsna Gattineni (International Journal of Pediatrics)
The identification of hematuria or proteinuria in an otherwise healthy child can cause anxiety to both the family and the pediatrician. The etiology of hematuria and proteinuria includes a long list of conditions, and detailed workup can be exhaustive, expensive and not essential in most of the patients. As will be described in this paper, most of the children with proteinuria or hematuria have a benign etiology. The primary role of the pediatrician is to identify hematuria/proteinuria, recognize the common causes of hematuria/proteinuria, and more importantly identify children with serious conditions that need referral to the nephrologist in a timely manner.